KNOWLEDGE OF THE INFLUENCE OF CIGARETTE SMOKE ON HEALTH IN THE COMMUNITY - Suari, Ani Osang; Kartono, Kartono Kartono (Hanoman Journal: Physical Education and Sport, 2024)
The effect of cigarette smoke is very dangerous for health and can cause various diseases such as lung cancer, asthma, heart disease, acute respiratory infections, and can even result in death because cigarette smoke contains many dangerous toxins. Lack of knowledge about the effects of cigarette smoke can harm human health. Each individual has a different response to the importance of knowing the effects of cigarette smoke on health so it is not surprising that there are still people who still think that exposure to cigarette smoke is not risky when exposed because they think that only people who smoke are at risk, even though It is passive smokers who have the highest risk. This research aims to determine the level of public knowledge regarding the effects of cigarette smoke on health. The research method used is by filling out a questionnaire. The sample in this study used 49 respondents. The data that has been collected is then analyzed using descriptive statistics. Based on data analysis, it was found that the level of public knowledge regarding the effects of cigarette smoke on health was predominantly very good.